Morfogénesis in vitro de Anthurium cubense (Araceae) - Warner Pineda, Jorge (1993)
A study of the in vitro morphogenesis of Anthurium cubense was done to develop a suitable micropropagation method. Some factors which affect callus formation from leaf segments are: leaf expansion percentage of the explant donor, leaf section from where the explants was taken, NH4NO3 and 2,4-D doses in the culture media, physical constitution of the media and photoperiod. Highest callogenesis percentages were observed in petioles explants taken from leaves with 25% expansion, cultured in Nitsch liquid medium plus 200 mg/l NH4NO3 and 0.5 mg/l 2,4-D and kept ion darkness. The callus produced roots but no buds. Under these conditions, the procedure developed for A. scherzerianum and A. andraeanum tissue culture is not suitable for this species.